The Influence of Family Business Creativity on Business Competition - Ujang Tajul; Hani Aliya Wardani; Dede Lela; Mira Nurfitriya; Azizah Fauziyah (UM Purwokerto Press, 2024)
In the era of globalization and evolving market dynamics, family businesses play an important role in the economy. The sustainability of family businesses often depends on their ability to innovate and compete effectively. Creativity is considered the key to gaining an edge in tough business competition. To analyze the influence of family business creativity on business competition. This research uses quantitative methods with a descriptive verification approach to collect and analyze data. Quantitative data was obtained through questionnaires distributed to family members involved in the family business. The object of this research is a company owned by Geulis Umbrella Craftsmen in Tasikmalaya City. These family companies were chosen to see business creativity in facing market competition. The results of this study show that business creativity has a major influence on family business competition, with competition as a significant mediator in this relationship. It is hoped that this research's implications will provide insight into the importance of business creativity in helping family businesses compete in traditional and modern markets.